ANALISIS PENGARUH DANA PIHAK KETIGA (DPK), NON PERFORMING FINANCING DAN TINGKAT SUKU BUNGA KRDIT TERHADAP PEMBIAYAAN BERBASIS BAGI HASIL (MUDHARABAH) PADA PERBANKAN SYARIAH INDONESIA - Herni Ali; M. Miftahurrohman (Tauhidinomics: Journal of Islamic Banking and Economics, 2015)
The purpose of this research is to analyze the influence of depositors’ Funds, non performing financing (NPF) and credit interest rates against volume of profit and loss sharing based financing (Mudharabah) in sharia banking in Indonesia during 2011-2014. The Population of this study is sharia banking (BUS) in Indonesia. The analysis method used is multiple linear regression. The result of this study show that : the depositors founds is significant positive influence on the mudharabah financing, non performing financing (NPF) does not influence to mudharabah financing and the average interest rate credit is significant positive influence to mudharabah financing. Then, testing in together show that the variabel depostors founds, non performing financing and the average interest rate of credit are significant influence as simultaneously to mudharabah financing